Complement-mediated serum bactericidal activity of antibodies elicited by the Shigella sonnei GMMA vaccine in adults from a shigellosis-endemic country: Exploratory analysis of a Phase 2a randomized study - Kapulu, Melissa C.; Nakakana, Usman; Sciré, Antonella S.; Sarakinou, Eleanna; Conti, Valentino; Rossi, Omar; Acquaviva, Alessandra; Necchi, Francesca; Obiero, Christina W.; Martin, Laura B.; Bejon, Philip; Njuguna, Patricia; et al. (Frontiers in Immunology, 2022)
Shigella is associated with a significant burden of disease worldwide among individuals of all ages and is the major cause of moderate and severe diarrhea in children under five years of age in low- and middle-income countries. Several candidate vaccines against Shigella species are currently under clinical development. The investigational 1790GAHB vaccine against Shigella sonnei is based on GMMA (Generalized Modules for Membrane Antigens) technology. The vaccine was well tolerated and induced high antibody levels in early-phase clinical trials in both Shigella-endemic and non-endemic settings. The present analysis assessed the bactericidal activity of antibodies induced by 1790GAHB in healthy Kenyan adults during a phase 2a, controlled, randomized study (NCT02676895). Participants received two doses of 1790GAHB 4 weeks apart containing either 1.5/25 µg or 6/100 µg O antigen/protein, or active comparator vaccines (Control). Serum bactericidal activity (SBA) against S. sonnei was assessed at pre-vaccination (D1), 28 days post-first dose (D29) and 28 days post-second dose (D57), using a luminescence-based assay. Most participants had SBA titers above the lower limit of quantification of the assay at D1. SBA geometric mean titers increased 3.4-fold in the 1.5/25 µg group and 6.3-fold in the 6/100 µg group by D29 and were maintained at D57. There was no increase in SBA geometric mean titers in the Control group. A strong correlation was observed between SBA titers and anti-S. sonnei lipopolysaccharide serum immunoglobulin G antibody concentrations (Pearson correlation coefficient = 0.918), indicating that SBA can effectively complement enzyme-linked immunosorbent assay data by indicating the functionality of 1790GAHB-induced antibodies.